Assessing Financial Risk Tolerance and Investment Decisions among Malaysians. An exploratory study. - Shanmuganathan, Suresh M. (2005)
Today there is a vast amount of information on financial markets and financial institutions but not much is known about individual investors. This study is designed to create a profile of Malaysian individual investor investment behavior by classifying them into risk tolerance categories. It also explores whether demographic, socioeconomic and psychological factors can be used to predict individual financial risk tolerance. Using a sample of 287 respondents it was determined that Malaysians in general are only slightly above average financial risk takers. Their most preferred vehicles of investment are Fixed Deposits and Unit Trust Funds. Using a regression model, gender, employment status, economic expectation, having liquid assets and ethnic backgrounds were found to be effective in differentiating among levels of risk tolerance among Malaysians. However,education and income were not found to be significant determinants of an individual’s attitude towards risk. Current investment behavior among Malaysians shows them to be generally non investment savvy and indicates probability of financial problems in their later years. Financial Institutions and the Government may have to play a bigger role in overcoming this shortcoming to avoid potential political, economic and social problems in the future. The findings of this study provides an initial basis for assessing financial risk tolerance among Malaysians which can be utilized for more comprehensive future research.